Brasil, 2016: cultura histórica digital e conceitos que constroem a história presente no ambiente escolar - Oliveira, Gabrielle Gomes (2024)
In the political and social landscape of 21st century Brazil, the government of President Dilma Rousseff between 2013 and 2016 became the subject of a dispute between the mainstream media, which legitimized the impeachment process. Historians denounced the action as a coup against democracy. Part of this conceptual dispute took place through social networks, driven by the various social movements in the so-called June 2013 Journey; these narratives reached different sectors of society and consequently the school environment, in which students, as members of their community, create and reproduce the discourses and concepts propagated by Digital Culture. This period marks a movement of change in the present that generates debate and impacts on the way students understand the past, the present and the future. In History Teaching, the question is: how can we promote students' historical education in a context of narrative and ideological disputes? To answer this question, we analyzed the discourses produced by historians in the book Historians for Democracy: the 2016 coup and the power of the past (2016), and the narratives published by G1, the Globo group's online news portal. This research aims to think about the relationship between concepts and historical learning of Present Time and Public History in the age of social media through the Brazilian political context in 2016, marked by disputes over narratives surrounding the impeachment of President Dilma Rousseff. In addition, a methodological proposal is presented that corresponds to a current demand for history teaching: the creation of a game about the different narratives produced about the period, from the perspective of history education and which incorporates the key concepts that form historical thinking.